EDUKASI CARA PENYIMPANAN SUPLEMEN DI WILAYAH KELURAHAN PENGGILINGAN - Niko Prasetya; Honey Iskandar; Fitri Savitri; Farizan Adriawan Zainal (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
There have been changes in people’s behavior since Covid-19 to prevent the spread of Covid-19. People are starting to realize the importance of consuming health supplements as a way to prevent the spread of Covid-19. However, this is still not in line with increasing public awareness of supplement storage. Storage of supplements that do not meet the standards can reduce their stability. This is the background for Community Service (PkM) activities in the Penggilingan Village area. Community Service activities were carried out through presentation of material to 74 residents from several RW. The results of data processing show an increase in community knowledge after the outreach was held, which was measured using pre-test and post-test scores. Keywords: knowledge, supplement, pre-test, post-test